2005
DOI: 10.1111/j.1442-200x.2005.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma carnitine levels in preterm infants with respiratory distress syndrome

Abstract: Low neonatal plasma carnitine levels in preterm infants with RDS may be due to decreased maternal-fetal transfer of carnitine or to increased consumption of carnitine in fetal lung tissue for surfactant synthesis. This could be a contributing factor in the pathogenesis of respiratory distress syndrome in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
3
6
1
2
Order By: Relevance
“…These results were concordant with those of previous studies that investigated serum L-carnitine levels in patients with or without RDS (2,3). In the present study, serum carnitine levels on day 1 were not associated with the gender of the patients, but did show a negative correlation with birth weight and a positive correlation with Apgar scores.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These results were concordant with those of previous studies that investigated serum L-carnitine levels in patients with or without RDS (2,3). In the present study, serum carnitine levels on day 1 were not associated with the gender of the patients, but did show a negative correlation with birth weight and a positive correlation with Apgar scores.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have demonstrated that carnitine is crucially involved in the development of RDS and the carnitine status of patients with RDS (2,3,19). The results of the present study indicated that the duration of mechanical ventilation and the requirement for surfactant therapy was significantly reduced in the groups that received L-carnitine treatment, as compared with the control groups.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations